Single-cell transcriptomics reveals hidden information in trypanosomatids - Abuchery, Bryan E. [UNESP]; Black, Jennifer A.; da Silva, Marcelo S. [UNESP] (Elsevier, 2022)
Dixenic parasites often encounter environmental extremes during the transition from vector to host. Preadapted transmission stages overcome these challenges to promote parasites' survival and ensure life cycle progression. Recently, Vigneron et al. and Briggs et al. used single-cell transcriptomics to investigate developmental stage specific gene expression patterns during parasite differentiation.
Keywords: scRNA-seq; transcriptome; transmission; Trypanosoma brucei